Comparative characteristics of cognitive disorders in patients with toxix (mercury) and vascular (atherosclerosclerotic) encepalopathy - Ye. V. Katamanova; O. L. Lakhman; O. K. Andreyeva; O. I. Shevchenko; T. N. Konstantinova (Бюллетень сибирской медицины, 2009)
The neurophysiological (the registration of induced potentials P300) and the psychological examinations of 70 patients, males, with chronic mercury intoxications (ChMI) and discirculatory encephalopathy (DE) have been performed with aim to reveal the features of cognitive disorders (CD). The study results have shown the presence of light CD and small demention in the patients of both groups, preferably, of subcork type for the patients with ChMI and preferably of cork type – for the patients with DE.